The Display of a Tourist Nation: Canada in Government Film, 1945-1959 - Apostle, Alisa (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2001)
AbstractBetween 1945 and 1959, the Canadian Government Travel Bureau experimented with the production of films to promote tourism that were shown in Canada and the US. As both propaganda and instruction, these films tell us much more than is immediately apparent, providing clues to post-war ideas about nation-building, economic reconstruction, citizenship, and the relationship between the state and consumer culture. Using established stereotypes of tourist venues and experiences, as well as creating tropes about government administration and the tourist “industry” itself, the political economy of the tourist trade was transformed in these films into a commodity for mass consumption.